(3LRA ef GdCMGOjK GdefJbGg GdYhGdi Yf TjhN GdHNGQis - (3CHh ESMGb EHQGgje Hf GdMSjf GdcSGFjs
(3ChdgG (B:s
(3GNHQfG GdTjN GdGeGe GHh GSMGb GHQGgje Hf GdeXaQ Hf GHQGgje GdMQHi GJi Ydjg She GdSHJ QGHY YTQ Pi GdMLI SfI KeGfi YTQI hSJeGFI ai efRdg HGdehUd s
(3BNQgG (B:s
(3bGd SeYJ YHO Gddg Hf YHGS jbhd bGd di QShd Gddg Udi Gddg Ydjg hSde(B:( (3jG ZdGe EjG c hGdfXQ ai GdfLhe aEfg jOYhG Edi GdcgGfI hEjGc hGdcdGe ai GdbOQ aEfg jOYhG Edi GdRfObI hGjGc hSH GUMGHi aEf SHge eYJHg BNQ GdLRA hGdMeO ddg QH GdYGdejf s
(3JHUQI GdYfhGf (B:s
(3QhGjI s
Keywords: (3GdMOjK h GdeUWdMs